P047 Rehabilitation-led management of sleep disordered breathing: adapting a model of care for a rehabilitation centre in Australia. (9th November 2022) - Graco, M; Weber, G; Joffe, D; Saravanan, K; Heriseanu, R; Whitehead, N; Alava-Bravo, K; DelaCruz, C; Sood, S; Curran, J; Kaumaitotoya, E; Pryor, J; et al.
Abstract: Introduction: Sleep disordered breathing (SDB) is highly prevalent in tetraplegia, yet most remain undiagnosed and untreated for the disorder. We have described the care models of three international SCI rehabilitation centres that are independently diagnosing and treating SDB, and distilled their common pathways into the SCISTAR (SCI Sleep disordered breathing Treatment & Assessment in Rehabilitation) model. The aim of this project was to adapt the SCISTAR model to suit the Royal Rehab Spinal Injuries Unit, and to prepare for the implementation of this new model of care. Methods: A clinical advisory group, consisting of researchers, rehabilitation and respiratory health professionals, met six times over eight months to: identify the multidisciplinary SDB clinical team, adapt the SCISTAR model, develop parameters for safe clinical practice, identify education needs, identify and acquire the necessary equipment. Results: The SDB clinical team consists of two rehabilitation consultants, two physiotherapists and four nurses. All patients with SCI will be assessed for SDB following admission. Assessments will include symptoms, spirometry and sniff nasal inspiratory pressure, and a Level 3 overnight sleep study (ResMed ApneaLink). Patients diagnosed with un-complicated SDB will be prescribed CPAP, which will be initiated and progressed on the ward. Screening for hypoventilation and predominant central sleep apnoea will occur throughout the pathway and if identified, patients will be referred to a specialist respiratory service. Comprehensive education and equipment has been provided. Conclusions: The new care model is currently being piloted for 12 months. A comprehensive evaluation has been developed.